Recent progress on artificial intelligence application for COVID-19 monitoring and mitigation system in Indonesia - Rosyid Ridlo, Al Hakim; Yanuar Zulardiansyah, Arief; Muhammad Haikal, Satria; Agung, Pangestu; Hexa A., Hidayah; Esa R. C., Putri; Aditia P., Hamid (2022)
COVID-19 is a serious public health issue in the world. The spread of COVID-19 has gone global. Indonesia is a country with a high rate of infectious cases worldwide. Multidisciplinary science also brings together to fight against COVID-19 in Indonesia. One of the important roles is artificial intelligence (AI). AI was also reported to help a vital role in public health. As a developing country, Indonesia also brings innovative AI approaches to help people with COVID-19, including classification, detection, diagnosis, prediction, telemedicine, and many more. This study elaborates the recent progress on AI application in Indonesia contributing to the fight against COVID-19 which has been reported in scientific papers/reports. Although research in this field is still not so developed, the existing innovations provide a new enthusiasm for public health and the benefits of the latest technology that can support human health, especially in facing a pandemic at Indonesia. It was found that there can be more research by utilizing AI approaches concerning public health and medicine in the future research work particularly in facing a pandemic condition.